Comprehensive Analysis and Expression Profiling of the OsLAX and OsABCB Auxin Transporter Gene Families in Rice (Oryza sativa) under Phytohormone Stimuli and Abiotic Stresses - Chai, Chenglin; Subudhi, Prasanta K. (Frontiers in Plant Science, 2016)
The plant hormone auxin regulates many aspects of plant growth and developmental processes. Auxin gradient is formed in plant as a result of polar auxin transportation by three types of auxin transporters such as OsLAX, OsPIN, and OsABCB. We report here the analysis of two rice auxin transporter gene families, OsLAX and OsABCB, using bioinformatics tools, publicly accessible microarray data, and quantitative RT-PCR. There are 5 putative OsLAXs and 22 putative OsABCBs in rice genome, which were mapped on 8 chromosomes. The exon-intron structure of OsLAX genes and properties of deduced proteins were relatively conserved within grass family, while that of OsABCB genes varied greatly. Both constitutive and organ/tissue specific expression patterns were observed in OsLAXs and OsABCBs. Analysis of evolutionarily closely related “gene pairs” together with organ/tissue specific expression revealed possible “function gaining” and “function losing” events during rice evolution. Most OsLAX and OsABCB genes were regulated by drought and salt stress, as well as hormonal stimuli [auxin and Abscisic Acid (ABA)], which suggests extensive crosstalk between abiotic stresses and hormone signaling pathways. The existence of large number of auxin and stress related cis-regulatory elements in promoter regions might account for their massive responsiveness of these genes to these environmental stimuli, indicating complexity of regulatory networks involved in various developmental and physiological processes. The comprehensive analysis of OsLAX and OsABCB auxin transporter genes in this study would be helpful for understanding the biological significance of these gene families in hormone signaling and adaptation of rice plants to unfavorable environments.